Transcriptional Landscape of Cardiomyocyte Maturation - Hideki Uosaki; Patrick Cahan; Dong I. Lee; Songnan Wang; Matthew Miyamoto; Laviel Fernandez; David A. Kass; Chulan Kwon (Cell Reports, 2015)
Decades of progress in developmental cardiology has advanced our understanding of the early aspects of heart development, including cardiomyocyte (CM) differentiation. However, control of the CM maturation that is subsequently required to generate adult myocytes remains elusive. Here, we analyzed over 200 microarray datasets from early embryonic to adult hearts and identified a large number of genes whose expression shifts gradually and continuously during maturation. We generated an atlas of integrated gene expression, biological pathways, transcriptional regulators, and gene regulatory networks (GRNs), which show discrete sets of key transcriptional regulators and pathways activated or suppressed during CM maturation. We developed a GRN-based program named MatStatCM that indexes CM maturation status. MatStatCM reveals that pluripotent-stem-cell-derived CMs mature early in culture but are arrested at the late embryonic stage with aberrant regulation of key transcription factors. Our study provides a foundation for understanding CM maturation.